Optimalisasi Pengambilan Keputusan Melalui Analisis Trend Penjualan pada Bisnis Retail Menggunakan Metode Least Square - S Suhardjono (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
The right business decisions are crucial in the business world to ensure business continuity and increase profitability. One important factor in making business decisions is sales sales. Businesses need accurate trading trade orders to fill inventory, improve sales performance, and maximize profits. This research case study focuses on the medical device retail business of CV. Independent Lakshmi. The company faces problems in replenishing inventory due to variable demand. The research objective is to analyze sales trends and customer buying interest using the least square method. The results showed that forecasting calculations yielded a MAPE value of 1% and there were sales trend analysis results, namely a total trend increase of 29.04% for karcher goods so that sales trend analysis could be contributed to the research site. Based on the results of system testing using Blackbox Testing, the results show that the system functionality is appropriate and valid.